INFLUENCE OF PRODUCT QUALITY AND BRAND TRUST ON CONSUMER SATISFACTION OF EMINA COSMETIC PRODUCTS - Ratih Siti Jamilah (Sekolah Tinggi Ilmu Ekonomi (STIE) Tri Dharma Nusantara Makassar, 2022)
The objective of this research was to determine the effect of product quality and brand trust on consumer satisfaction of Emina's cosmetic products on Emina consumers in Tanjung Morawa Village A Dusun II Deli Serdang Regency. This research used a quantitative descriptive approach. The population were 80 respondents in which the entire population was sampled with a sampling technique by using a saturated sampling technique. Based on the results of the research that has been done, get the simultaneous test (f test) of the two independent variables on the dependent variable. The results showed that the variables of product quality and brand trust had a significant effect on consumer satisfaction, it was seen from the value of fobserved (204.580) > ftable (3.12) with a significant value of 0.000 <0.05. With an R square value of 0.842. This means that the effect of variable X1 and variable X2 on variable Y is 84.2%, while the remaining 15.8% is affected by other variables.